1985
DOI: 10.1161/01.res.56.6.801
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and adrenal receptors for atrial natriuretic factor in the rat.

Abstract: Previous studies have shown that atrial natriuretic factor, a powerful vasorelaxant of precontracted vessels, inhibits the secretion of aldosterone stimulated by angiotensin II, adrenocorticotropic hormone, and potassium. We now report the presence of specific binding sites for atrial natriuretic factor in rat blood vessels (mesenteric and renal arteries) and adrenal capsules. Radioiodinated synthetic atrial natriuretic factor bound to a single class of high-affinity (KD = 0.1 nM) low-capacity receptors in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…'251-ANF, whereas nonrelated peptide hormones do not significantly displace radioactive ANF. The observed dissociation constant of 125I-ANF to brain microvessels corresponds to a high-affinity site similar to those obtained in other vascular tissues for larger vessels such as rabbit aorta (3), rat aorta (21), rat mesenteric arteries, and renal arteries (5) and in bovine aortic smooth muscle and endothelial cells (22).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…'251-ANF, whereas nonrelated peptide hormones do not significantly displace radioactive ANF. The observed dissociation constant of 125I-ANF to brain microvessels corresponds to a high-affinity site similar to those obtained in other vascular tissues for larger vessels such as rabbit aorta (3), rat aorta (21), rat mesenteric arteries, and renal arteries (5) and in bovine aortic smooth muscle and endothelial cells (22).…”
Section: Resultssupporting
confidence: 83%
“…4). It was observed that 125I-ANF displayed a rate of association with a half-life of about 5 was shown by dissociation with the addition of native ANF to a final concentration of 1 ,uM (Fig. 4).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The inhibitory action of atrin on aldosterone release is dependent on an intact intramolecular disulfide bridge (79), similar to the structural requirement for smooth muscle relaxation (33). Specific receptors for atrin have been demonstrated in membranes prepared from adrenal glomerulosa (44,64), and receptor binding is again critically dependent on an intact disulfide bridge (44). Reduction of plasma aldosterone levels in response to atrin infusion has also been documented in anesthetized dogs (12) and in conscious rats (96 (98), although a direct effect of atrin on renin secretion by renal cortical slices has also been reported (99).…”
Section: Actions On Aldosterone Biosynthesis and Secretionmentioning
confidence: 86%
“…Atrial pacing (38) and paroxysmal atrial tachyarrhythmias (60) elevate circulating atrin concentrations and, in patients with congestive heart failure, plasma-atrin levels were markedly elevated above normal levels (59), indicating that chronic elevation of atrial pressures may lead to hypersecretion ofatrin. Reports ofatrin concentrations in rat plasma have been variable, with levels ranging from 20 to 550 pM (35,37,61 Ala-Arg-Thr--Gn-Gly-Leu-Leu-Gln--Phe-Ala-Leu-Leu-Leu-Leu-Phe-Ser-Val (gly) (ile)j(his) (64), and rabbit aorta (65), from rat and rabbit kidney (65) and cultured renal epithelial (LLC PK,) cells, derived from pig kidney (65).…”
Section: Control Ofatrin Secretionmentioning
confidence: 99%